Study of reading habits 1984 - Southern Halland - Weibull, Lennart (University of Gothenburg, 1993)
This survey forms part of the research program ´Dagspresskollegiet´. The target group of this survey was the inhabitants of three municipalities in southern Halland: Halmstad, Hylte and Laholm. Most of the questions are replications of questions asked in previous readership studies, i.e. questions concerning reading habits, subscriptions of papers, reading interests and background variables such as gender, age, education and party preference. There were also questions not asked in previous surveys. In this survey the respondents were asked if they had enough knowledge in English to follow an English or American program without Swedish subtitles. Another question dealt with who had the greatest influence on the choice of morning paper. A battery of questions dealt with the local paper Hallands-Posten specifically.

This survey forms part of the research program ´Dagspresskollegiet´. The target group of this survey was the inhabitants of three municipalities in southern Halland: Halmstad, Hylte and Laholm. Most of the questions are replications of questions asked in previous readership studies, i.e. questions concerning reading habits, subscriptions of papers, reading interests and background variables such as gender, age, education and party preference. There were also questions not asked in previous surveys. In this survey the respondents were asked if they had enough knowledge in English to follow an English or American program without Swedish subtitles. Another question dealt with who had the greatest influence on the choice of morning paper. A battery of questions dealt with the local paper Hallands-Posten specifically.
Läsvanestudien 1984 - Södra Halland
Keywords: internal politics; inrikespolitik; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap